(untitled) (Historia, 2025)
Books reviewed: Henning Melber, The Long Shadow of German Colonialism: Amnesia, Denialism and Revisionism Marion Sparg, Guilty and Proud: An MK Soldier’s Memoir of Exile, Prison and Freedom Ronnie Kasrils and Fidelis Hove, Comrade and Commander: The Life and Times of Joe Modise Sandra Swart, The Lion’s Historian: Africa’s Animal Past Victor Muchineripi Gwande, Manufacturing in Colonial Zimbabwe, 1890-1979: Interest Group Politics, Protectionism, and the State Neil Roos, Ordinary Whites in Apartheid Society: Social Histories of Accommodation David Boucher and Bongani Ngqulunga, eds, Reappraising the Life and Legacy of Jan Smuts